Cornea biomechanics and biometric evaluations in immunoglobulin G4-related ophthalmic disease - Kenneth Ka Hei Lai; Fatema Mohamed Ali Abdulla Aljufairi; Jake Uy Sebastian; Xulin Liao; Wanxue Chen; Zhichao Hu; Yingying Wei; Ruofan Jia; Cheuk Wah; Andy Chi On Cheng; Joyce Kar Yee Chin; Andrew KT Kuk; et al. (PLoS ONE, 2026)
Purpose To evaluate the corneal biomechanical and biometric properties in immunoglobulin G4-related ophthalmic disease (IgG4-ROD) patients. Setting Ethnic Han Chinese biopsy-proven IgG4-ROD patients from a territory wide cohort and sex-, age-, smoking- and lens status-matched healthy controls. Design A case-controlled (1:1) study. Methods Corvis ST analyzer and IOL Master 700 biometry assessment. Results Sixty-seven eyes from 67 patients with IgG4-ROD (41 = males), aged 63.9 ± 13.1 years and 67 right eyes from 67 healthy ethnically Han Chinese controls were recruited. IgG4-ROD eyes were associated with a more negative applanation 2 velocity (−0.30 versus −0.27 m/s, P = 0.0143), and reduced radius of curvature (7.48 versus 7.98 mm, P = 0.0136). There was no difference in intraocular pressure, applanation 1 length, applanation 1 velocity, applanation 2 length, deformation amplitude and peak distance. Corneal astigmatism was greater in IgG4-ROD eyes (−1.2 versus −0.9 D , P = 0.0132), and the deep axis is along 90.2 degree. There is no difference in the steep and flat keratometry, deep axis, lens thickness, cornea thickness, and anterior chamber depth. Conclusions We found multiple corneal changes in biomechanics and fine structures in a cohort of biopsy-proven IgG4-ROD with potential long-term implications in ocular surface functions. A longitudinal follow-up would be useful to identify the clinical implications and observe if these changes improve with treatments.